Rationale design of pancreatic a-amylase inhibitor - Phua, Jeremy Joon How (2015)
Type 2 diabetes mellitus is a chronic metabolic disorder characterized by loss of glycaemic control. Despite the increasing incidence of type 2 diabetes mellitus, limited oral antidiabetic agents are available. Furthermore, the potency of some drugs is unjustifiable due to the level of side-effects. Therefore, there is a need for development new drugs. In this study, we designed a drug lead by replacing part of as1 with the binding motif of Tendamistat. Tendamistat is a proteinaceous inhibitor that is secreted by Streptomyces Tendae. Tendamistat is prone to digestion hence it cannot be used as an oral drug. As1 is a peptide extracted from the plant - Allatide Scholaris. As1 belongs to cysteine knot mini-peptide family that has digestion and heat resistance properties. Because of its unique properties, we selected and used As1 as the drug template to develop our drug lead. Porcine pancreatic α-amylase was used as model system due to its similarity to human pancreatic α-amylase. After simulating for 100 ns, we docked the designed peptide with porcine pancreatic α-amylase and found out that the designed peptide binds deeper into the binding pocket. Binding energy analysis suggested that the design peptide binds with lower binding energy as compared to Tendamistat.